Gambaran Karakteristik Pasien Diabetes Melitus Tipe 2 Rawat Inap di Rumah Sakit Pertamina Cirebon Tahun 2019 - Ferlitasari, Shavira Norma; Wuryanto, Moh Arie; Sutiningsih, Dwi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Diabetes mellitus is a degenerative disease that occurs due to the unbalanced amount of insulin in the body. Diabetes Mellitus is a disease that is hidden before symptoms appear such as hunger, thirst, and frequent urination. Based on data from the Cirebon District Health Office, the number of diabetes mellitus cases in the inpatient hospital in 2015 ranked 10th as much as 1.5%. And in 2018 Pertamina Hospital Cirebon had a total of 250 cases of Diabetes Mellitus patients. The research objective was to describe the characteristics of type 2 diabetes mellitus patients hospitalized at Pertamina Cirebon Hospital. This type of research is a descriptive quantitative approach with a cross-sectional design. The sample size in this study used the Slovin formula and obtained 37 respondents. The results showed 94.6% of the patients were more than 39 years old, 54.1% were male, 43.2% had a high school education background, and 29.7% worked as housewives. As many as 51.4% of the patient's knowledge level was high, 78.3% had a bad patient behavior level, and 81.1% had high patient severity. There is a relationship between age, level of education, occupation, descent, and inpatient DM patients at Pertamina Hospital Cirebon.